Implementation of sustainable technologies in the construction industry - a bibliometric analysis (Research, Society and Development, 2022)
The construction industry (ICC) is one of the sectors that suffer the most pressure when it comes to sustainable development. However, it is a very important branch for the world economy in view of its global production and participation in the GDP of countries over the years. In recent years, the demand for the adoption of more sustainable practices, both in developed and developing countries, in this field has increased due to the opportunity of this segment to contribute in an intelligent way through the use of natural resources. In this sense, taking into account that among the 17 sustainable development goals (SDGs), three have direct impacts for the ICC, through a bibliometric review, this research aims to evaluate the implementations of sustainable technologies in this sector, using the concepts of SDGs For this, searches were made for scientific articles, in databases such as Web of Science, ProQuest, Scielo, Taylor & Francis, Scopus and Science Direct, in order to find articles that dealt with sustainable practices used in civil construction. The results show that in relation to technologies, the topic Energy Efficiency and water resources management appear as topics with the highest number of publications in recent years.